Value of branded education - Tomas Krabec; Romana Čižinská (Financial Internet Quarterly, 2020)
The objective of the paper is to examine value creation in private higher education. The results of the research are to be applied in reasonable structuring of study programs and courses and for creating profitable business and marketing strategies for private universities. From a student perspective, higher education is a project that must generate a positive net present value. In the pre-investment and investment phases, students see cash outflows and opportunity costs. In the third phase, the project generates benefits that take the form of cash inflows from employment or doing business in the relevant field. The value of the study program from the perspective of a private university is produced by the present value of the future cash flows generated by the investment in the study program and its administration and operation. The main cash inflows are created by tuition revenues and the main cash outflows are brand-related investments and personnel costs. The market equilibrium occurs when the value of a degree program from the perspective of a private university corresponds to the total aggregate net present value of a degree program at a private university from a student perspective.
Keywords: M21; C61; D82; 330; Brand Valuation; Valuation of Intangibles; Net Present Value; Higher Education